A FIB-STEM Study of Strontium Segregation and Interface Formation of Directly Assembled La0.6Sr0.4Co0.2Fe0.8O3-δ Cathode on Y2O3-ZrO2 Electrolyte of Solid Oxide Fuel Cells. Issue 7 (1st January 2018) - He, Shuai; Saunders, Martin; Chen, Kongfa; Gao, Haifeng; Suvorova, Alexandra; Rickard, William D. A.; Quadir, Zakaria; Cui, C. Q.; Jiang, San Ping
Abstract : Electrode/electrolyte interface plays a critical role in the performance and stability of solid oxide fuel cells (SOFCs). Here, interface formation, Sr segregation and reaction of directly assembled La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) cathode on barrier-layer-free Y2 O3 -ZrO2 (YSZ) electrolyte are studied at 1000 mAcm −2 and 750°C using focused ion beam and scanning transmission electron microscopy (FIB-STEM) techniques. The results indicate that polarization promotes the formation of LSCF/YSZ interface with a high level of periodicity and symmetry but no amorphous phases or solid solutions. Further polarization induces the Sr segregation and diffusion toward the LSCF/YSZ interface, forming Sr rich layer (SRL, primarily SrO) at LSCF and YSZ interface. Segregated Sr species are highly mobile and deposition of SrO occurs at the LSCF/YSZ interface as well as on the YSZ electrolyte surface. The reaction between SRL and YSZ is fast, forming SrZrO3 secondary phase. The growth of SrZrO3 phase at the interface are affected by the crystallography lattice plane orientation of the YSZ electrolyte, forming a coherence interface between SrZrO3 and YSZ electrolyte. Further polarization accelerates Sr segregation and formation of the SrZrO3 reaction layer, leading to the disintegration of LSCF structure at the interface. The results indicate that chemical reaction between LSCF and YSZ occurs at 750°C under polarization conditions, kinetically induced by the segregated SrO at the interface and on the YSZ electrolyte surface.